Answer:
![\textsf{1)} \quad f(x)=-x+3](https://img.qammunity.org/2023/formulas/mathematics/high-school/li2llcxmsg2f82k6ug1wh87m047c6ynpdv.png)
2) A = (3, 0) and C = (-3, 0)
![\textsf{3)} \quad g(x)=x^2-9](https://img.qammunity.org/2023/formulas/mathematics/high-school/9x4ah6vw7mp18r3knqcjrogt2lp053x04m.png)
4) AC = 6 units and OB = 9 units
Explanation:
Given functions:
![\begin{cases}f(x)=mx+c\\g(x)=ax^2+b \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dzs3l0tpfxk67mhtys7ix9i4yf472im5wg.png)
Part (1)
Given points:
As points H and T lie on f(x), substitute the two points into the function to create two equations:
![\textsf{Equation 1}: \quad f(-1)=m(-1)+c=4 \implies -m+c=4](https://img.qammunity.org/2023/formulas/mathematics/high-school/d2qiygqoijw48ok4hc9rwju7qlx9qm8hbc.png)
![\textsf{Equation 2}: \quad f(4)=m(4)+c=-1 \implies 4m+c=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/1yu1ncxbcedqjc0zp0w12i8z45282h9t3g.png)
Subtract the first equation from the second to eliminate c:
![\begin{array}{r l} 4m+c & = -1\\- \quad -m+c & = \phantom{))}4\\\cline{1-2}5m \phantom{))))}}& = -5}\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/yvwaqv1y99g2lso1euqkm1hszr9m8vba6s.png)
Therefore m = -1.
Substitute the found value of m and one of the points into the function and solve for c:
![\implies f(4)=-1(4)+c=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/tyvrs2t8zg6rbrksvp9ihrp2spvi57ewc4.png)
![\implies c=-1-(-4)=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/9iyyxkwj1eorstyi7csl6kvbdcsc3m4nut.png)
Therefore the equation for function f(x) is:
![f(x)=-x+3](https://img.qammunity.org/2023/formulas/mathematics/high-school/6y617xuuqntc8qpgiq1qoqchgeqsbonej9.png)
Part (2)
Function f(x) crosses the x-axis at point A. Therefore, f(x) = 0 at point A.
To find the x-value of point A, set f(x) to zero and solve for x:
![\implies f(x)=0](https://img.qammunity.org/2023/formulas/mathematics/college/y8dbiiuqecj5hijf80zxqkkymr7agul0nz.png)
![\implies -x+3=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/eslh62cy2hepnjnnhf10v2n2drqrv5mjx4.png)
![\implies x=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/mzf4ih6guqait6h2fqn9pc6o8r041andur.png)
Therefore, A = (3, 0).
As g(x) = ax² + b, its axis of symmetry is x = 0.
A parabola's axis of symmetry is the midpoint of its x-intercepts.
Therefore, if A = (3, 0) then C = (-3, 0).
Part (3)
Points on function g(x):
Substitute the points into the given function g(x) to create two equations:
![\textsf{Equation 1}: \quad g(3)=a(3)^2+b=0 \implies 9a+b=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/4b2zl9denyjd8xdnda4gcdo208bqgrdk5i.png)
![\textsf{Equation 2}: \quad g(1)=a(1)^2+b=-8 \implies a+b=-8](https://img.qammunity.org/2023/formulas/mathematics/high-school/qto6jvyyufyppzibor3titw3y7w7jma418.png)
Subtract the second equation from the first to eliminate b:
![\begin{array}{r l} 9a+b & = \phantom{))}0\\- \quad a+b & =-8\\\cline{1-2}8a \phantom{))))}}& = \phantom{))}8}\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/edwxk3vs4kap0la19rqy9c5wc7mhsxdrg4.png)
Therefore a = 1.
Substitute the found value of a and one of the points into the function and solve for b:
![\implies g(3)=1(3^2)+b=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/r5denmwoe22xeakqdq4xi0v3gwo0oh6ohy.png)
![\implies 9+b=0\implies b=-9](https://img.qammunity.org/2023/formulas/mathematics/high-school/m41zqysr4mozehjhonkgpsa7yvzqgqf6x7.png)
Therefore the equation for function g(x) is:
![g(x)=x^2-9](https://img.qammunity.org/2023/formulas/mathematics/high-school/kn6ys8md5ttydpi9if72y8hyn4w2xebmoa.png)
Part 4
The length AC is the difference between the x-values of points A and C.
![\implies x_A-x_C=3-(-3)=6](https://img.qammunity.org/2023/formulas/mathematics/high-school/uy8cnczveayulfc2t8qg26bkqmfi9egfnz.png)
Point B is the y-intercept of g(x), so when x = 0:
![\implies g(0)=(0)^2-9=-9](https://img.qammunity.org/2023/formulas/mathematics/high-school/cn57phhugkaxtxaeh19jugtp0efeschp40.png)
Therefore, B = (0, -9).
The length OB is the difference between the y-values of the origin and point B.
![\implies y_O-y_B=0-(-9)=9](https://img.qammunity.org/2023/formulas/mathematics/high-school/xx4fz72hcbgkbfkilpeconwz6hc8ijrur6.png)
Therefore, AC = 6 units and OB = 9 units